Composition of the secretion from the eccrine sweat glands of the cat's foot pad - Foster, K. G. (1966)
1. The sweat composition from the cat's foot pad was examined at various rates of secretion. Sodium pentobarbitone or chloralose anaesthesia were used. 2. Cat's pad sweat contains lactate, glucose is almost absent, and the sodium and chloride concentrations increased with increasing sweat rate. In these respects the secretion resembles human eccrine sweat. 3. The sodium, chloride, and potassium concentrations are much higher than in human sweat; also the potassium level decreased with increasing rate. Consequently, whereas human sweat is hypotonic with respect to the plasma, cat's pad sweat is slightly hypertonic with respect to the plasma even at low rates of secretion. In contrast to human sweat glands, which produce a slightly acidic secretion containing ammonia, cat's pad sweat glands produce an alkaline secretion containing bicarbonate. Also in contrast to human sweat, lactate levels decreased with increasing sweat rate.